PENERAPAN MODEL PEMBELAJARAN KOOPERATIF NUMBERED HEAD TOGETHER BERBANTUAN MEDIA PAPAN PERKALIAN UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA - Aulia, Aziqri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by students' lack of understanding of mathematics, especially multiplication, which is one of the basics of number operations. In addition, during the learning process, educators tend to use expository learning models and occasionally use learning media, which causes students to become bored during the learning process. This study is an experimental study with a quasi-experimental research design, using a pretest-posttest control group design. In this design, there are two groups, namely the experimental group and the control group, which are then given a pretest to determine the initial conditions and whether there are differences between the experimental class and the control class. Then, at the end of the learning process, both classes were given a posttest to determine the students' understanding of mathematical concepts. The instrument used in this study was an essay-type test. Data collection techniques used observation, testing, and documentation. Data analysis techniques used normality tests, homogeneity tests, N-Gain tests, and hypothesis testing using SPSS. The results of this study indicate that, first, the application of the Numbered Head Together Cooperative Model assisted by multiplication boards in mathematics learning had a significant effect on students' conceptual understanding, with a posttest average score of 12.57. Second, learning using the expository learning model yielded a posttest average score of 11.42. Third, in the t-test results, the sig value (2-tailed) was 0.000, so the sig value < 0.05 and a t-count value of 4.979 > t-table 0.686. Therefore, based on the decision-making basis in the t-test, Ha is accepted and Ho is rejected, meaning that there is an increase in students' understanding of mathematical concepts with the application of the Numbered Head Together Learning Model assisted by a multiplication board.